Vortex-field enhancement through high-threshold geometric metasurface - Qingsong Wang; Yao Fang; Yu Meng; Han Hao; Xiong Li; Mingbo Pu; Xiaoliang Ma; Xiangang Luo (Opto-Electronic Advances)
Intense vortex beam is expected to empower captivating phenomena and applications in high power laser-matter interactions. Currently, the superposition of multiple vortex beams has shown the unique ability to tailor and enhance the vortex field. However, traditional strategies to generate such beams suffer from large volume or/and low laser-induced damage threshold, hindering the practical widespread applications. Herein, a single high-threshold metasurface is proposed and experimentally demonstrated for the generation and superposition of multiple collinear vortex beams. This scheme takes advantage of the high conversion efficiency of phase-only modulation in the metasurface design by adopting the concept of a sliced phase pattern in the azimuthal direction. An optical hot spot with an enhanced intensity and steady spatial propagation is experimentally achieved. Moreover, femtosecond laser-induced birefringent nanostructures embedded in silica glass are utilized as the building block with high optical efficiency. Transmittance greater than 99.4% in the near-infrared range and laser-induced damage threshold as high as 68.0 J/cm2 (at 1064 nm, 6 ns) are experimentally verified. Considering these remarkable performances, the demonstrated high-threshold metasurface has promising applications in a host of high-power laser fields.